PENGEMBANGAN APLIKASI MANAJEMEN SURAT BERBASIS WEB DI SMK KP 3 MAJALAYA - COMPUTING INFORMATIKA; Rustiyana (COMPUTING | Jurnal Informatika, 2021)
Management and archiving, especially the management of incoming and outgoing letters at SMK KP 3 Majalaya, has so far run well although it is still done simply. Both by way of writing manuals in the mail book and with the help of a simple mail management application. In this way it is certainly inefficient because it requires very thick books and large archive storage cabinets especially if to record in a long period of time and officers will have difficulty in finding certain mail documents that have been stored because the search process is done by checking one by one in the filing storage cabinet. Mail Management application is a system to facilitate the management process, especially correspondence in SMK KP 3 Majalaya. The conclusion of this research is to help develop the existing mail management system in SMK KP 3 Majalaya from a conventional system and simple application into a web-based computerized system using PHP and MySQL.